Pengelolaan Air Bersih dengan Metode Sederhana di Desa Kualu Kecamatan Tambang - Sri Hardianti; Zurrahmi ZR; Yoana agnesia; Fahmi Iqbal Firmananda (Journal of Social and Community Service, 2025)
The availability of clean water is a fundamental necessity that greatly affects public health and quality of life. Kualu Village, Tambang Subdistrict, Kampar Regency, continues to face problems related to clean water quality, particularly from well water sources that are colored, odorous, and potentially contaminated. This community service activity aimed to improve access to and the quality of clean water through the application of appropriate technology in the form of a simple water filtration system that is easy for the community to operate and maintain. The implementation methods included an initial survey, technology design, training, mentoring, and evaluation. The results showed an increase in community knowledge and skills in managing clean water, as well as improvements in the physical quality of water. This activity is expected to contribute to improving environmental health and the sustainability of clean water management in Kualu Village.